Smad4 promotes diabetic nephropathy by modulating glycolysis and OXPHOS. (9th January 2020) - Li, Jinhua; Sun, Yu Bo Yang; Chen, Weiyi; Fan, Jinjin; Li, Songhui; Qu, Xinli; Chen, Qikang; Chen, Riling; Zhu, Dajian; Zhang, Jinfeng; Wu, Zhuguo; Chi, Honggang; et al.
Abstract: Diabetic nephropathy (DN) is the leading cause of end‐stage kidney disease. TGF‐β1/Smad3 signalling plays a major pathological role in DN; however, the contribution of Smad4 has not been examined. Smad4 depletion in the kidney using anti‐Smad4 locked nucleic acid halted progressive podocyte damage and glomerulosclerosis in mouse type 2 DN, suggesting a pathogenic role of Smad4 in podocytes. Smad4 is upregulated in human and mouse podocytes during DN. Conditional Smad4 deletion in podocytes protects mice from type 2 DN, independent of obesity. Mechanistically, hyperglycaemia induces Smad4 localization to mitochondria in podocytes, resulting in reduced glycolysis and oxidative phosphorylation and increased production of reactive oxygen species. This operates, in part, via direct binding of Smad4 to the glycolytic enzyme PKM2 and reducing the active tetrameric form of PKM2. In addition, Smad4 interacts with ATPIF1, causing a reduction in ATPIF1 degradation. In conclusion, we have discovered a mitochondrial mechanism by which Smad4 causes diabetic podocyte injury. Synopsis: This study reveals a mitochondrial role of Smad4 in the pathogenesis of diabetic nephropathy. Hyperglycemia induces Smad4 localization to mitochondria of podocytes. Smad4 depletion in podocytes protects mice from glomerulosclerosis in type 2 diabetes models. Smad4 depletion promotes glycolysis and OXPHOS activity under high glucose conditions. Hyperglycemia promotes the interaction between Smad4 and PKM2, thereby increasing PKM2 tetramerization and activity. Smad4 directly interacts with ATP synthase inhibitor ATPIF1 and inhibits it degradation. Abstract : This study reveals a mitochondrial role of Smad4 in the pathogenesis of diabetic nephropathy.